Highlights aus dem Haags Gemeentemuseum. - Staatliche Kunsthalle, Baden-Baden; Haags Gemeentemuseum, Den Haag; Brehm, Margrit; Bühler-Teuber, Ulrike; Constant; Heil, Axel; Locher, J.L.; Mueller, Jessica; Möckel, Birgit; Schimpf, Simone; Teuber, Dirk; Van Es, Jonieke; et al. (Baden-Baden : Staatliche Kunsthalle Baden-Baden, 1998)
Appel, Karel ; Arp, Hans (Jean) ; Birza, Rob ; Braque, Georges ; Campendonk, Heinrich ; Constant ; Daniels, René ; van Donge, Kees ; Dubuffet, Jean ; Dumas, Marlene ; Ernst, Max ; Fauconnier, Henri Le ; Federle, Helmut ; van Gogh, Vincent ; van Heemskerk, Jacoba ; van der Heyden, J.C.J. ; Hussem, Willem ; Jorn, Asger ; Kandinsky, Wassily ; Ket, Dick ; Kruyder, Herman ; van der Leck, Bart ; Leger, Fernand ; Maaskant, Jan ; Macke, August ; Millares, Manolo ; Modersohn-Becker, Paula ; Mondriaan, Piet ; Morandi, Giorgio ; Morellet, François ; Munoz, Lucio ; Niehaus, Kasper ; Nijland, Dirk ; Pechstein, Max ; Permeke, Constant ; Picasso, Pablo ; Van Rysselberghe, Theo ; Saalborn, Louis ; Schmidt-Rottluff, Karl ; Schoonhoven, Jan ; Schouten, Marien ; Schuhmacher, Wim ; Schwitters, Kurt ; Segal, Arthur ; Signac, Paul ; Sluyters, Jan ; De Smet, Gustave ; Toorop, Charley ; Toorop, Jan ; van Velde, Bram ; Verhoef, Toon ; Van de Woestyne, Gustave
biografie
Highlights aus dem Haags Gemeentemuseum, Staatliche Kunsthalle, Baden-Baden, 1998
Duits
boek